Underachieving Secondary Students’ Mathematical Learning Experiences - Paudel, Krishna Chandra; Ghimire, Shree Prasad (Journal of Mathematics Education, 2026)
Underachievement in mathematics is a major issue in Nepalese secondary education, as national assessments indicate that most students achieve below the proficiency level. This research paper examined the experiences of four eleventh-grade underachieving students to gain insights into the cognitive, emotional, and contextual hindrances influencing their mathematical education. Guided by socio-cultural and motivational theories, a qualitative interpretive design was utilized in this study. Data were collected through several narrative interviews, accompanied by classroom observations and field notes. The findings revealed that students regarded mathematics as abstract and daunting, resulting in decreased self-efficacy, avoidance behaviors, and increased anxiety. Teacher-focused teaching methods with memorization, and restricted personalized assistance diminished student engagement. Socio-economic limitations and a lack of family support exacerbated these difficulties. The results indicated that underachievement in mathematics was associated with a combination of psychological, educational, and socio-cultural elements, emphasizing the importance of learner-focused teaching, contextual methods, and emotional support to promote inclusive math learning environments in Nepal.